Reactive Processing of Acrylic-Based Thermoplastic Composites: A Mini-Review - Bodaghi, Masoud; Park, Chung Hae; Krawczak, Patricia (Frontiers in Materials, 2022)
The demand for thermoplastic composites is continuously increasing because these materials offer many advantages over their thermoset counterparts, such as high toughness, long storage time, easy repairing and recycling, and ability to be thermoformed and heat-welded. However, the manufacturing of thermoplastic composite parts using liquid composite moulding techniques (e.g. resin transfer moulding, vacuum assisted resin transfer moulding …) is often tricky in the case of melt processing where high temperature and pressure should be chosen to impregnate the fibre reinforcement because of the high melt viscosity of thermoplastics. These issues may be overcome by means of reactive processing where a fibrous preform is first impregnated by a low viscosity mono- or oligomeric precursor and the polymerization of the thermoplastic matrix then occurs in-situ. This article draws a state of the art on the manufacturing characteristics of continuous fibre reinforced acrylic-based reactive thermoplastics (e.g. polymethymethacrylate (PMMA) such as Elium), which are becoming more and more popular compared to other fast curing thermosets and thermoplastics for in-situ polymerization. Techniques for the in-situ polymerization of methymethacrylate monomers, characterization and modelling of the rheological properties and polymerization kinetics, and some manufacturing related issues such as polymerization shrinkage are reviewed. Particular features of the use of reactive PMMA in different manufacturing techniques of continuous fibre reinforced composites and potential industrial applications are also introduced. Finally, some perspectives for the academic research and industrial development are proposed.